(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
The article provides a scientific analysis of the use of artificial intelligence (AI) technologies in the early diagnosis of dental caries in pediatric dentistry. In recent years, highly accurate neural networks and automated image processing systems have significantly improved the ability to detect caries at its initial stages. Compared to traditional clinical examinations and radiography, AI-based diagnostics offer advantages such as speed, precision, and reduced subjective errors. Research findings show that AI-supported diagnosis enhances the effectiveness of preventive dentistry in children, reduces the need for invasive treatments, and plays a crucial role in improving oral health.